DESIGN OF MICROWAVE FILTER USING THE SEQUENTIAL METHOD - TIOE , CHIEN (IRC, 2019)
Microwave filters are used to provide frequency selectivity which is an essential component in Microwave system. Mobile communication is also one of the applications of Microwave filter, has become an integral part of our society, one of the most impact technologies in our daily life. Therefore, in order to meet the expectation, a way to design and deploy to manage to overcome the bandwidth shortage in the next generation of mobile networks which is 5G mobile network. For 5G mobile network, need a larger physical size and costly. During the design process, by using the conventionalimethoditoidesignimicrowave filters are lack of considerationiof theicross - coupling and loadingieffect. Thus, the finalijointidesign filtersimay not metithe design requirements, even though the design requirements have meet each design signal element. Sequential method is also known as group delay method. Sequential method is a method where the filter design will separate into a small design of stages which can reduce the time optimizing.